Reformulating Small Molecules for Cardiovascular Disease Immune Intervention: Low-Dose Combined Vitamin D/Dexamethasone Promotes IL-10 Production and Atheroprotection in Dyslipidemic Mice - Ospina-Quintero, Laura; Jaramillo, Julio C.; Tabares-Guevara, Jorge H.; Ramírez-Pineda, José R. (Frontiers in Immunology, 2020)
The targeting of proinflammatory pathways has a prophylactic and therapeutic potential on atherosclerotic cardiovascular diseases (CVD). An alternative/complementary strategy is the promotion of endogenous atheroprotective mechanisms that are impaired during atherosclerosis progression, such as the activity of tolerogenic dendritic cells (tolDC) and regulatory T cells (Treg). There is a need to develop novel low cost, safe and effective tolDC/Treg-inducing formulations that are atheroprotective and that can be of easy translation into clinical settings. We found that apolipoprotein E-deficient (ApoE-/-) mice treated with a low-dose combined formulation of Vitamin D and Dexamethasone (VitD/Dexa), delivered repetitively and subcutaneously (sc) promoted interleukin-10 (IL-10) production by dendritic cells and other antigen presenting cells in the lymph nodes draining the site of injection and the spleens. Expectedly, the treatment also increased the numbers of IL-10-producing CD4+ T cells. Concomitantly, the frequency of IFNγ-producing CD4+ and CD8+ T cells in the spleen, and the IFNγ response of splenocytes to polyclonal stimulation ex vivo were lower after VitD/Dexa treatment, indicating a reduced proatherogenic Th1 response. Interestingly, VitD/Dexa-treated mice had smaller atherosclerotic lesions, with reduced lipid content and lower inflammatory infiltrate of macrophages and T cells in the aortic root. No hypolipidemic or antioxidant effect could be detected, suggesting that a dominantly immunomodulatory mechanism of atheroprotection was engaged under the low-dose sc VitD/Dexa conditions used. Finally, no evidence of clinical, biochemical or immune toxicity was observed in treated ApoE-/- mice and, most importantly, C57BL/6 mice latently infected with Leishmania parasites and treated with an identical VitD/Dexa dose/scheme showed no clinical or microbiological signs of disease reactivation, suggesting the absence of general immunosuppression. Altogether, these results indicate that a non-toxic, non-immunosuppressive, low-dose of VitD/Dexa, administered subcutaneously and repetitively, exerts atheroprotective effects in dyslipidemic mice, apparently due to the induction of an IL-10-producing network of lymphoid and myeloid immune cells. These well known, widely available, and inexpensive small molecules can be easily co-formulated into a simple and accessible agent with a potential use as a prophylactic or therapeutic immune intervention for CVD and other chronic inflammatory diseases.